Personalizm ekonomiczny i jego zasady w ujęciu G.M.A. Gronbachera - Urgacz, Paweł (Annales. Etyka w Życiu Gospodarczym, 2008)
The dialog that has been conducted for a few years between a group of Christian social thinkersand economists on moral aspects of economic activity has led to the creation of a new science disciplinecalled economic personalism. On the one hand it stipulates the need to express economic processeswithin ethical categories, on the other hand it perceives the necessity to elaborate a strong economictheory. Economic personalists refer to the works of those thinkers who returned to the basic economicinspiration as a field belonging predominantly to moral philosophy. This school is sometimes calledthe Austrian School or the School of Classical Liberalism.A significant role in the economic personalism development was performed by its forerunnerswho noticed what was lacking in the previous interpretations of Catholic social thought. Amongthe there are John Paul II, Michael Novak, Rocco Buttiglione and the Acton Institute.The intellectual sources of economic personalism are mainly related to concept of personalismdeveloped in Poland. Its specific thesis, seen in the maxim that “each person ought to be affirmed forthe sake of it itself” also relates to the economic life.Economic personalists formulate principles that are spokesmen in order to promote a free societybuilt on virtues. They are expressed in the following way: pre-eminence of a human being: economyand human dignity; human capital: creation and creativity; dignity of human work: calling forenterprise, integral development of human being, manufacture and personalism, participation, economiccommon wealth, helpfulness, market restrictions; preferential option for the poor: solidarity and socialequity.